Upaya Meningkatkan Motivasi dan Hasil Belajar IPA Materi Klasifikasi Makhluk Hidup Melalui Penerapan Model Pembelajaran Inkuiri Terbimbing (Guided Inquiri) pada Siswa Kelas VII A MTs Negeri Batang - Nani Nursani (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2021)
The research entitled Efforts to increase Motivation and Science Learning Outcomes for Classification of Living Things Through the Application of Guided Inquiry Learning Models for Class VII A MTs Negeri Batang, is Classroom Action Research. The purpose of this research is to apply the Guided Inquiry learning model, so that it can increase students' learning motivation and learning outcomes. This classroom action research was carried out in 2 cycles, each cycle consisting of 3 meetings. This research showed that the motivation of students from the initial conditions, cycle 1 and cycle 2 continued to increase. Percentage of student learning outcomes who complete and exceed the KKM (from 50% to 91.67%). The indicator of the success of this Classroom Action Research is, if the percentage of students whose learning scores have reached a minimum of 80%. then it has been successful. The conclusion of this Classroom Action Research is that students' motivation and learning outcomes have increased after learning is applied through the Guided Inquiry learning model.